REPRESENTASI FEMINISME PADA TOKOH UTAMA DALAM FILM “GANGUBAI KATHIAWADI” (Analisis Semiotika Charles Sanders Peirce) - Sari Dewi, Ni Kadek Aprilia; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2023)
Film is part of mass communication, which is often used as a medium to describe social life in society. Films are often used to address important issues that need to be discussed or shared with the public. The film also talks about the role of women in the media, which focuses on the struggle to maintain gender equality for all women in the world. This research contains a framework for liberal and radical feminism in fighting for societal issues that emphasize equality of opportunity and rights for every individual, especially women, as well as resistance of oppression by men are represented in a film called “Gangubai Kathiawadi”. This film represents this phenomenon through a social issue drama genre film. This research uses descriptive qualitative research with semiotic analysis of Charles Sanders Peirce's Triangle of Meaning Theory. The results of this research are that “Gangubai Kathiawadi” is an Indian film that dominantly represents liberal feminism. Keywords: Feminism, Film, Gangubai Kathiawadi, Semiotics.